Ołtarz główny i obraz "Wniebowzięcia Najświętszej Marii Panny” w kościele szadkowskim – w świetle prac konserwatorskich - Królewski, Jacek (Biuletyn Szadkowski, 2010)
The paper provides an overview of conservation work carried out in 1996–1998 in the parish church in Szadek, involving renovation of the main altar. The text takes the form of reminiscences of the conservation team members rather than providing detailed descriptions of the different stages of this project. The author has focused on unexpected, surprising facts and developments which occurred in the course of the renovation work. In the final part of the paper the history of the altar is presented against the background of the town’s history.